2018
DOI: 10.1002/jbio.201800020
|View full text |Cite
|
Sign up to set email alerts
|

Joint tagging assisted fluctuation nanoscopy enables fast high‐density super‐resolution imaging

Abstract: In fluctuation-based optical nanoscopy, investigating high-density labeled subcellular structures with high fidelity has been a significant challenge. In this study, based on super-resolution radial fluctuation (SRRF) microscopy, the joint tagging (JT) strategy is employed to enable fast high-density nanoscopic imaging and tracking. In fixed cell experiment, multiple types of quantum dots with distinguishable fluorescence spectra are jointly tagged to subcellular microtubules. In each spectral channel, the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Therefore, like other immuno-based technic PLA present a certain level of background, easily quantifiable by using single probe, secondary antibodies only, protein mutant and/or non-existing interaction detection. PLA can detect an interaction up to a 40 nm distance 36 and enables super high resolution immunofluorescence microscopy, which can distinguish molecules at a similar distance 37 . Although PLA cannot detect real-time protein-protein interaction, quantification of PLA signals of different GATA1 complexes in sequential stages of ES cell differentiation improves our understanding on the temporal changes of these complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, like other immuno-based technic PLA present a certain level of background, easily quantifiable by using single probe, secondary antibodies only, protein mutant and/or non-existing interaction detection. PLA can detect an interaction up to a 40 nm distance 36 and enables super high resolution immunofluorescence microscopy, which can distinguish molecules at a similar distance 37 . Although PLA cannot detect real-time protein-protein interaction, quantification of PLA signals of different GATA1 complexes in sequential stages of ES cell differentiation improves our understanding on the temporal changes of these complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, Betzig () has predicted that the optical properties of the emitters can be used to separate them to different dimensions. Previously, we have demonstrated that the inverse multiplexing in the spectral domain can improve the spatiotemporal resolution of intensity blinking‐based super‐resolution techniques (Zeng et al ., ; Zeng et al ., ). Herein, taking advantage of lifetime‐blinking property and wide‐field lifetime imaging technique, we demonstrated the possibility of achieving super‐resolution through lifetime blinking nature with numerical simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they are also notorious for their blinking [23]. However, by taking advantage of their blinking characteristic, the possibility of QDs being used in super-resolution imaging has been demonstrated, such as in stochastic optical reconstruction microscopy (STORM) [24], SOFI [25] and SRRF [26]. The FEAST method is based on fluorescent fluctuation, and therefore the blinking characteristic of QDs could be applied to FEAST.…”
Section: Feast Imaging Of Qd605 Labeled Samplementioning
confidence: 99%